Rice and Magic: A Cultural History from the Precolonial World to the Present - Aguilar, Filomeno V, Jr (Archīum Ateneo, 2013)
Beliefs in rice spirits were integral to the magical worldview of the precolonial inhabitants of the Philippine islands. Under Spanish colonialism, rice became a staple but it underwent disenchantment and symbolic marginality. By the 1870s rice production fell short relative to demand. Twentieth-century initiatives to address persistent shortages culminated in the 1960s Green Revolution, which further altered the rice plant and ushered in the age of practicality. Because rice production cannot be fully controlled, farmers still deploy culturally meaningful strategies to deal with uncertainties. The old meanings of rice for commensality have also proven resilient and reveal peculiarly Filipino ways.